Inovasi Alat Perajang Otomatis sebagai Upaya Peningkatan Produktivitas Usaha Keripik Singkong di Kelurahan Jedong - Wijaya, Handika Setya; Anggraini, Sinar Perbawani Abrina; Indana, Luthfi (Jurnal Pemberdayaan Masyarakat, 2025)
Mr. Bawi's cassava chips MSME in Wagir District, Malang Regency, faced challenges in financial management, marketing, and food hygiene, coupled with the use of semi-manual chopping tools that were less hygienic and time-consuming. The solutions offered included business management governance training such as simple financial reports, the use of financial applications, BEP and SWOT analysis, marketing through e-commerce, and hygiene and sanitation training, along with the innovation of an automatic cassava chopping tool. This activity aimed to increase production, human resource quality, and market expansion to support increased income. As a result, chip production increased by 74% to 192 kg per 2 hours, knowledge of BEP and SWOT analysis increased from level 1 to 4.7, quality control and hygiene from level 1 to 4.9, and marketing and e-commerce communication from level 1 to 4.